2020
DOI: 10.15561/20755279.2020.0605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of static balances level on competitive performance indicators of athletes 17-21 years old in beach volleyball

Abstract: Background and Study Aim. To determine the influence of the level of static balance on the competitive activity of athletes aged 17-21 in beach volleyball. Material and Methods. The study involved athletes aged 17-21 years, who play beach volleyball in the Kherson region. The research was focused on the main indicators: the total number of serves, passes, tactical strikes, blocks, and how the development of static balance affects the level of their performance. Results. Acrobatic exercises in train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…ey divide the joints of the human body, which can be divided into the head, trunk, upper and lower left arm, upper and lower right arm, upper and lower left leg, and upper and lower right leg. Related scholars have proposed a very classic graph structure algorithm [14]. e author uses a collection of multiple parts to express the human body, and there are certain spatial constraints between these parts.…”
Section: Related Workmentioning
confidence: 99%
“…ey divide the joints of the human body, which can be divided into the head, trunk, upper and lower left arm, upper and lower right arm, upper and lower left leg, and upper and lower right leg. Related scholars have proposed a very classic graph structure algorithm [14]. e author uses a collection of multiple parts to express the human body, and there are certain spatial constraints between these parts.…”
Section: Related Workmentioning
confidence: 99%
“…The authors found out that coordination indicators improve with age and are positively affected by sports. Other studies have shown that the level of coordination indicators development is closely correlated with the effectiveness of competitive activities in volleyball [7] and handball [8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors believe that serve (standing serve, jump serve, float jump serve) and spike have different performance profiles based on technique, player role, and age. Other studies consider: tactics of team actions [10]; attack tactics [11,12]; competitive activity [13,14]. In general, the WoS database presents a fairly wide range of research areas in beach volleyball.…”
mentioning
confidence: 99%